Transformasi Nilai-Nilai Budaya Islam di Sulawesi Selatan - Syamhari Syamhari (Rihlah : Jurnal Sejarah dan Kebudayaan, 2015)
The aims of this research is to describe and to known the impact of Islamic cultural transformation in South Sulawesi. According to the theory of Islamic cultural transformation, this reasearch will be split in two sides. Firstly, this reasearch will talking about Islamic cultural transformation in education side. This transformation are marked by appearing of the new tradition in educational management, such as pesantren kilat, Anak Saleh Education Studio (SPAS) and also pesantren educational institute. Secondly, this reasearch is talking about Islamic cultural transformation in economic side. It happened, when the Islamic culture came to Indonesia, and brought a new way of trading. Of course, the new way of trading was embraced by the Islamic value which had made a lot of profit to the local traders. In conclusion, Islamic cultural transformation in South Sulawesi had given a positive impact to the progress of education, economic and local wisdom.